SISTEM NOTIFIKASI KEBAKARAN GEDUNG MENGGUNAKAN TELEGRAM - Feri Siswoyo Hadisantoso (LPPM Politeknik Enjinering Indorama, 2019)
Building fires are events that cause damage that can occur at any time and cannot be predicted. Fire results in material loss and loss of life. Factors causing fires include electrical short circuit, gas leakage and human negligence. In addition, further treatment is with the help of fire trucks. However, the community is often too late in contacting and providing information about the conditions to the officers, causing the fire to get bigger so that tools are needed to monitor and warn everyone in the room and to the officers to send messages in case of fire. DHT22 sensor module is used to detect temperature and humidity, the temperature read range of the sensor is 0-100 ° C and humidity is 0-100%. The MQ-02 sensor is used to detect the concentration of flammable gases in the air and smoke and the flame sensor is used to detect fire, the system uses a raspberry pi3 controller and a telegram application for monitoring and notification systems.